1955
DOI: 10.1002/path.1700690138
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus and its pathogenic action

Abstract: PLATE XCIV) IN 1951 Gledhill and Andrewes described a flterable agent which produced fatal hepatitis in mice. It was believed to have originated in P strain mice*, since it produced hepatitis in VSBS(VS) strain mice t when suspensions of viscera of P mice were passed blindly several times in VS mice. Later, Gledhill et al. (1952) showed that this agent consisted of two flbrable components ; a relatively labile one which was identified as Eperythrozoiin coccoides (Schilling, 1928, quoted by McCluskie andNi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
1
2

Year Published

1956
1956
1974
1974

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 2 publications
4
14
1
2
Order By: Relevance
“…Although in weanlings not infected with E. coccoides small liver lesions were seen only irregularly, in all instances typical lesions were found on histological examination. In tissues from thymectomized wasting mice which showed liver lesions Dr. Niven stated that the histological appearances were compatible with the presence of a mouse hepatitis virus, probably MHV-1, as described by Gledhill, Dick, and Niven (10). It should be noted in this context that we have not detected E. coccoides in blood smears taken from thymectomized wasting C3H/Bi, C57BL, hybrid C57BL X C3H/Bi, or TO mice.…”
Section: 0supporting
confidence: 69%
“…Although in weanlings not infected with E. coccoides small liver lesions were seen only irregularly, in all instances typical lesions were found on histological examination. In tissues from thymectomized wasting mice which showed liver lesions Dr. Niven stated that the histological appearances were compatible with the presence of a mouse hepatitis virus, probably MHV-1, as described by Gledhill, Dick, and Niven (10). It should be noted in this context that we have not detected E. coccoides in blood smears taken from thymectomized wasting C3H/Bi, C57BL, hybrid C57BL X C3H/Bi, or TO mice.…”
Section: 0supporting
confidence: 69%
“…In viral hepatitis in mice, necrosis of parenchymal cells has not been ob served histologically until 48-72 h after viral inoculation [21,25,35]. The studies reported here with the aid of the electron microscope have shown early changes that occur within 24 h following EMC virus inoculation.…”
Section: Discussionmentioning
confidence: 57%
“…E. coccoides was present in 10-6 dilutions of the yolk sac from two of the lqter passages. Gledhill, Dick & Andrewes (1952) and Gledhill, Dick & Niven, 1955), using a similar diluent, found that E. coccoides could be passaged in dilutions of a suspension of mouse liver and spleen. The successful cultivation of Eperythrozom coccoides in embryonated eggs suggests that these are at present the most suitable media for the cultivation of other species of Eperythrozoon and perhaps of Haemobartonella.…”
Section: Propagatim and Preservatiolz Of E Coccoides 349mentioning
confidence: 97%